2019
DOI: 10.1002/cti2.1074
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL‐34 correlates with macrophage infiltration and prognosis of diffuse large B‐cell lymphoma

Abstract: Objectives Infiltration of macrophages through the tyrosine kinase receptor CSF1R is a poor prognosis factor in various solid tumors. Indeed, these tumors produce CSF1R ligand, macrophage colony‐stimulating factor (M‐CSF) or interleukin‐34 (IL‐34). However, the significance of these cytokines, particularly, the newly discovered IL‐34 in haematological malignancies, is not fully understood. We therefore analysed the role of IL‐34 in diffuse large B‐cell lymphoma (DLBCL), the most common subtype of malignant lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
2
11
0
Order By: Relevance
“…Therefore, the hypothesis was that CSF1R in DLBCL identified only TAMs. In DLBCL, high CD163-positive TAMs have been associated with poor prognosis of the patients [9,10,12], which is the same result seen by gene expression in the LLMPP series. Nevertheless, the presence of a B-cell pattern was not expected.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Therefore, the hypothesis was that CSF1R in DLBCL identified only TAMs. In DLBCL, high CD163-positive TAMs have been associated with poor prognosis of the patients [9,10,12], which is the same result seen by gene expression in the LLMPP series. Nevertheless, the presence of a B-cell pattern was not expected.…”
Section: Discussionsupporting
confidence: 68%
“…The tumor-associated macrophages (TAMs) are of special interest because the ones with an M2-like phenotype have tumor-promoting capabilities [9], which involve tumor proliferation, invasion, angiogenesis, metastasis, and suppression of anti-tumor immunity [10,11]. In DLBCL, it has been reported that high numbers are associated with a poor prognosis of DLBCL [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages were analyzed for the expression of KLF2, KLF4, c-Myc, c-Maf, MafB, or PU.1 mRNA followed by the normalization to the mRNA level of GAPDH, as described previously 37 . In brief, RNA was isolated using the ISOGEN II reagent (Nippon Gene, Tokyo, Japan), and each cDNA was prepared using M-MLV RT (Invitrogen).…”
Section: Real-time Rt-pcrmentioning
confidence: 99%
“…The receptor tyrosine kinase CSF1R (also known as Fms) pathway regulates migration, differentiation, proliferation, and survival at varying degrees of different tissue-resident macrophages and monocytes in mammals and zebrafish ( Oosterhof et al, 2018 ; Kuil et al, 2019 ). Recent studies have implicated a role for this pathway in macrophage recruitment in disease, including the assembly of tumor-associated macrophages in various cancers ( Noyori et al, 2019 ; Lin et al, 2019 ; Zins et al, 2018 ; Baghdadi et al, 2016 ; Baghdadi et al, 2018 ). Of particular interest IL-34 is elevated and implicated in the inflammation process of several inflammatory diseases including rheumatoid arthritis, inflammatory bowel disease, and Sjogren’s syndrome ( Ciccia et al, 2013 ; Hwang et al, 2012 ; Moon et al, 2013 ; Chemel et al, 2012 ; Boulakirba et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%